Detection of high levels of anti-α-galactosyl antibodies in sera of patients with Old World cutaneous leishmaniasis: a possible tool for diagnosis and biomarker for cure in an elimination setting. Issue 14 (9th October 2014) - AL-SALEM, WALEED S.; FERREIRA, DANIELA M.; DYER, NAOMI A.; ALYAMANI, ESSAM J.; BALGHONAIM, SALAH M.; AL-MEHNA, AHMED Y.; AL-ZUBIANY, SALEEM; IBRAHIM, EL-KEIR; AL SHAHRANI, ALI M.; ALKHUAILED, HAMED; ALDAHAN, MOHAMMED A.; AL JARALLH, ABDULAZIZ M.; et al.
SUMMARY: In the Kingdom of Saudi Arabia (KSA), Old World cutaneous leishmaniasis (CL) is mainly caused by Leishmania major and Leishmania tropica parasites. Diagnosis of CL is predominately made by clinicians, who at times fail to detect the disease and are unable to identify parasite species. Here, we report the development of a chemiluminescent enzyme-linked immunosorbent assay (CL-ELISA) to measure the levels of anti- α -galactosyl antibodies in human sera. Using this assay, we have found that individuals infected with either Leishmania spp. had significantly elevated levels (up to 9-fold higher) of anti- α -Gal IgG compared to healthy control individuals. The assay sensitivity was 96% for L. major (95% CI; 94–98%) and 91% for L. tropica (95% CI; 86–98%) infections and therefore equivalent to restriction fragment length polymorphism-polymerase chain reaction analysis of parasite ITS1 gene. In addition, the assay had higher sensitivity than microscopy analysis, which only detected 68 and 45% of the L. major and L. tropica infections, respectively. Interestingly, up to 2 years following confirmed CL cure individuals had 28-fold higher levels of anti- α -Gal IgG compared to healthy volunteers. Monitoring levels of anti- α -Gal antibodies can be exploited as both a diagnostic tool and as a biomarker of cure of Old World CL in disease elimination settings.